Disorders of Childhood: Development and Psychopathology, 3rd Edition - Robin Hornik Parritz; Michael F. Troy (Cengage Learning, 2017)
To provide you with a meaningful framework for learning and understanding, this text is written with the whole child in mind and presents disorders in the context of typical development and developmental pathways. Multiple themes recur throughout the text: the continuity between typical and atypical development; risk and resilience; complex models of psychopathology; children in relationships over time; children in larger social contexts (ethnic backgrounds, neighborhoods, cultures); and the holistic nature of development (thinking about the whole child and his or her abilities and strengths as well as his or her disorder or areas of struggle). This developmental psychopathology approach, which reflects the most up-to-date understanding of child and adolescent psychopathology, will teach you to think about disorders in terms of the individual children who are coping with distress and dysfunction.